Future workscapes : emerging business trends and innovations - Paliszkiewicz, Joanna; Varoğlu, Demet; Kulykovets, Olena (International perspectives on equality, diversity and inclusion ;, 2025)
In an era where technological advancements, shifting societal norms, and global challenges are fundamentally reshaping the landscape of work, Future Workscapes emerges as a pivotal publication. The second of two parts, this volume delves into critical aspects of the modern workplace by analyzing emerging business trends and innovations and business practices. Chapters focus on branding and consumers, career commitment, work satisfaction, strategic management schools, management theory, internal communication, and more. Through qualitative research and case studies, authors provide insights into creating technologically advanced, human-centric and inclusive organizations. Both Part A and B of Future Workscapes offers an in-depth exploration of the evolving work environment and human resource strategies, addressing the urgent need for organizations to adapt to rapid changes, fostering environments that are not only technologically advanced but also human-centric, sustainable, and inclusive.